Existence Bali Governor Regulation No. 1 of 2020 Concerning Governance of Bali Fermented and or Distilled Beverages - Wedha, Yogi Yasa; Wijaya, I Made Hendra; Artajaya, I Wayan Eka; Permadi, Putu Lantika Oka (Formosa Journal of Multidisciplinary Research, 2024)
This research discusses the issue of the existence of gubernatorial regulations Bali No. 1 of 2020 concerning the Governance of Balinese Fermented and/or Distilled Drinks, what is the Legal Certainty and Benefits. The aim of the research is to see to what extent the existence of Bali Gubernatorial Regulation No. 1 of 2020 can regulate the issue of governance of Balinese fermented and/or distilled drinks and whether this regulation can provide legal protection, legal certainty and benefits as expected. The problem that will be discussed is related to the Management of Balinese Fermented and/or Distilled Drinks Efficacy and Benefits for the people of Bali. Normative legal research methods with a statutory approach, historical approach, and conceptual approach. The research results show that the Governor based on his authority and function can issue Governor regulations, but materially, the substance regulated therein cannot conflict with the substance that has been regulated in the statutory regulations above. This study shows that the substances regulated in PERGUB1/2020 is contrary to the above regulations (PERPRES 74/2013) therefore, based on the principle of Lex Superior Derogat Legi Inferiori, Gubernatorial Regulation No. 1/2020 cannot normatively be enforced as a product of binding statutory regulations, thus its existence cannot provide legal protection and benefits for the community.